2019
DOI: 10.17576/jsm-2019-4811-11
|View full text |Cite
|
Sign up to set email alerts
|

Sumber Penyumbang Karbon ke dalam Sedimen Dataran Rumput Laut di Muara Sungai Pulai, Johor, Malaysia

Abstract: ABSTRAKTerdapat banyak kajian karbon biru yang menggunakan kaedah penjejak isotop untuk mendapatkan maklumat mengenai sumbangan sumber bahan organik (OM) di dalam sedimen. Objektif kajian ini terbahagi kepada dua iaitu untuk mengetahui sumbangan sumber kepada takungan OM dan untuk membandingkan keberkesanan penggunaan dua jenis isotop stabil (δ 13 C dan δ 15 N) atau satu jenis isotop stabil (δ 13 C) dalam menentukan sumbangan OM di kawasan persampelan. Sampel rumput laut, makroalga, seston dan epifit di kawas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Because of the relatively large mangrove catchment area of the Sungai Pulai system, any allochthonous terrestrial matter would likely be buffered and filtered from entering the river upstream and, therefore, be minimally transported downstream and into the estuary. The overlapping signatures between terrestrial OM and mangroves were distinguished by using dual isotope tracers of δ 13 C and δ 15 N, thus lowering uncertainties and increasing the robustness of the Bayesian mixing model (Greiner et al, 2016; Hidayah, Rozaimi, & Nadzir, 2019). Furthermore, the mean (± SD ) endmember δ 13 C for mangrove plants is −31.4‰ ± 0.4‰ (Table 1), calculated based on mangrove tissue signatures ranging from 29.8‰ to 33.8‰ ( n = 12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the relatively large mangrove catchment area of the Sungai Pulai system, any allochthonous terrestrial matter would likely be buffered and filtered from entering the river upstream and, therefore, be minimally transported downstream and into the estuary. The overlapping signatures between terrestrial OM and mangroves were distinguished by using dual isotope tracers of δ 13 C and δ 15 N, thus lowering uncertainties and increasing the robustness of the Bayesian mixing model (Greiner et al, 2016; Hidayah, Rozaimi, & Nadzir, 2019). Furthermore, the mean (± SD ) endmember δ 13 C for mangrove plants is −31.4‰ ± 0.4‰ (Table 1), calculated based on mangrove tissue signatures ranging from 29.8‰ to 33.8‰ ( n = 12).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, sediment OC sequestration of macroalgae can be demonstrated if macroalgal‐derived biomass in the sediment is empirically quantified. Studies have demonstrated that macroalgal‐derived OC was simultaneously buried with seagrass‐ and mangrove‐derived OC (e.g., Chen et al, 2017; Hidayah, Rozaimi, & Nadzir, 2019; Tuntiprapas et al, 2019) and that the dominant primary producer of a coastal habitat may not necessarily contribute to the dominant OM pool (Hidayah, Rozaimi, & Nadzir, 2019; Oreska et al, 2018). Furthermore, the role of macroalgae in contributing toward the OM pool correlates with the ecological condition of the habitat.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown the presence of refractive carbon compounds [129], which may be the essential organic carbon reservoir in the oceans [130]. According to some findings, organic carbon extracted from macroalgae is buried alongside organic carbon derived from seagrass [131][132][133]. Although macroalgae (especially kelp organisms) contribute significantly to the carbon cycle along the coast, most species and regions still lack accurate carbon fixation estimates [134,135].…”
Section: Blue Carbon Ecosystems As Carbon Sequestration and Sinksmentioning
confidence: 99%
“…Initially, algal meadows were not considered a possible blue carbon contributor (Duarte et al 2005) due to their limited long-term potential for carbon sequestering (Smale et al 2018). However, recent studies have demonstrated that thanks to the source-sink mechanism (transport of a large amount of biomass of algae from euphotic coastal waters to the seabed), macroalgae can contribute signi cantly to the vertical ux of organic carbon and its sequestration in ocean sediment (Oreska et al 2918;Hidayah et al 2019).…”
Section: Introductionmentioning
confidence: 99%